Poéticas da carne: a necropolítica no encalço da poesia contemporânea brasileira - Lima, Felippe Nildo Oliveira de (2021)
The master‘s research focuses on two poetic anthologies released in 2019 by Cult magazine: Poemas para ler antes das notícias, organized by Alberto Pucheu, and Quando a delicadeza é uma afronta, curated by Tarso de Melo. The reality of the deaths perpetrated by the Brazilian State and its institutions, such as the army and the police, and by civil society against blacks, women, indigenous people and LGBTQIA+, in terms of what Achille Mbembe (2016) calls ―necropolitics‖, crosses strongly the sensibilities of poets, and it is placed in their texts as a question that politically confronts the word and work with poetry in our time, more specifically in 9 poems that i bring for analysis and reading in this dissertation. Therefore, the general objective of the research is to discuss the search developed by Brazilian poetry in the last decade to constitute itself as a countermode or reaction to necropolitics and the erasure of its killings. Although the poems enunciate very recent deaths, it is inevitable, in their analysis, to relate the current political context of death in the country to the history of traumas and wounds since the beginning of the colonial project. Starting from this genesis of the State violence in Brazil, the work still follows the following aspects: understand how contemporary poets have named and located the voids left by bodies victimized by political deaths and gratuitous hate crimes motivated by racism and by LGBTQIA+phobia; we perceive how a language of poems resonates in the pathetic, the tragic and the horror, how to approach the nameless real suffered by the flesh of the bodies of pain torn apart; seek political propositions in the poems that perpetuate the lives, bodies and memories of necropower victims beyond the short time of existence that have an imagery reception of everyday catastrophes and newspaper news, demarcating the political commitments of recent poetry not only with the dead, but also with the life of the killable ones who insist on surviving.